Process measure aimed at reducing time to haemorrhage control: outcomes associated with Code Crimson activation in exsanguinating truncal trauma. Issue 4 (11th February 2020) - Tovmassian, David; Hameed, Ahmer M.; Ly, Jessie; Pathmanathan, Nimalan; Devadas, Michael; Gomez, David; Hsu, Jeremy M.
Abstract: Background: Major trauma activation is a process that mobilizes personnel and resources required to care for severely injured patients. Exsanguinating truncal trauma patients require an additional response beyond major trauma activation aimed at expediting haemorrhage control. To address this requirement, 'Code Crimson' (CC) activation was developed. Our aim was to examine the performance of CC activation as a process measure in the identification and management of patients with exsanguinating truncal trauma. Methods: Retrospective cohort study (2010–2015) of all adult patients who underwent operative intervention within 6 h of arrival for truncal trauma was performed. Patients were classified into: (i) major haemorrhage (assessment of blood consumption score ≥2, base deficit ≥5 and/or transfusion ≥5 U of red blood cells pre‐/intra‐operatively), or (ii) no major haemorrhage. We evaluated the proportion of patients with/without major haemorrhage in which a CC was activated as well as time to operating theatre across groups. Results: A total of 210 patients were included with a median Injury Severity Score of 20 (interquartile range (IQR) 9–29) and overall mortality of 13%. Eighty‐nine patients were classified as major haemorrhage and 61 patients underwent CC activation. The majority of CC activations (92%) fulfilled major haemorrhage criteria (sensitivity 63%, specificity 96%). Time to theatre was lower in those with CC activation with median time of 23 min (IQR 15–39.5) versus non‐CC with median of 95 min (IQR 43–180, P < 0.001). Conclusion: CC was primarily activated in patients with major haemorrhage and led to a decrease in time to theatre for patients with operative truncal trauma. Abstract : Exsanguinating truncal trauma patients require a response above and beyond major trauma activation aimed at expediting haemorrhage control. To address this requirement, 'Code Crimson' activation was developed as a process measure in the identification and management of patients with exsanguinating truncal trauma.